The Anti-atherosclerotic Effect of Paeonol against Vascular Smooth Muscle Cell Proliferation by Up-regulation of Autophagy via the AMPK/mTOR Signaling Pathway - Wu, Hongfei; Song, Aiwei; Hu, Wenjun; Dai, Min (Frontiers in Pharmacology, 2018)
Introduction: Paeonol (2’-hydroxy-4’-methoxyacetophenone), isolated from moutan cortex, is an active component and has been shown to have anti-atherosclerotic and anti-proliferation effects on vascular smooth muscle cells (VSMCs). However, the possible role of Paeonol in protecting against VSMC proliferation as related to autophagy has yet to be elucidated. Methods: The athero-protective effects of Paeonol were evaluated in apoE-/- mice. The effects of Paeonol on VSMC proliferation and autophagy were examined by staining α-SMA and LC3II spots in the media layer of apoE-/- mice, respectively. CCK8 and BrdU assays were used to investigate the effects of Paeonol on cell proliferation in vitro. The autophagic levels in VSMCs were evaluated by detecting LC3II accumulation and p62 degradation by immunoblot analysis. To investigate if Paeonol could prevent VSMCs proliferation through autophagy induction, we tested the change in autophagy and cell proliferation by inhibition of autophagy. The levels of the AMPK/mTOR pathway in autophagy regulation were detected by immunoblot analysis. An AMPK inhibitor and si-AMPK transfection in VSMCs was used to confirm whether AMPK activity plays a key role in autophagy regulation of Paeonol. Result: In vivo experiments confirmed that Paeonol restricted atherosclerosis development and decreased the amount of VSMCs in the media layer of apoE-/- mice. Paeonol increased protein levels of LC3II and the presence of autophagosomes in the media layer of arteries, which implies that Paeonol may induce VSMCs autophagy in vivo. Paeonol showed potential in inhibiting ox-LDL-induced proliferation in vitro experiments. Paeonol dose-dependently enhanced the formation of acidic vesicular organelles and autophagosmomes, up-regulated the expression of LC3II and increased p62 degradation. The autophagy inhibitor CQ obviously attenuated Paeonol-induced autophagy and the anti-proliferation effect in VSMCs. In addition, Paeonol induced phosphorylation of AMPK and reduced phosphorylation of mTOR. An AMPK inhibitor reversed the Paeonol-induced p-mTOR/mTOR decrease. Paeonol induced LC3II conversion, increased p62 degradation and inhibited cell proliferation in VSMCs, the effects of which were abolished by si-AMPK. Conclusion: These results imply that Paeonol inhibits proliferation of VSMCs by up-regulating autophagy, and activating the AMPK/mTOR signalling pathway, providing new insights into the anti-atherosclerosis activity of Paeonol.